Simultaneous effects of ferulic and vanillic acids on peroxidase and phenylalanine ammonia-lyase in soybean (Glycine max) roots - Suzuki, L. S.; Herrig, V; Ferrarese, MDL; Rodrigues, J. D.; Ferrarese, O. (Ferdinand Berger Soehne, 2003)
Simultaneous effects of ferulic (FA) and vanillic (VA) acids on peroxidase (POD, EC 1.11.1.7) and phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) activities on soybean (Glycine max (L.) MERR.) root growth were analyzed. Three-day-old seedlings were cultivated in nutrient solution containing FA or VA (0.5 mM; 1.0 mM or equimolar mixtures) for 48 h. Acting alone, both compounds (at 0.5 or 1.0 mM) decreased root length (RL), fresh weight (FW), dry weight (DW) and increased soluble POD and cell wall (CW)-bound POD activities. At 1.0 mM, FA increased (but VA decreased) the PAL activity. Acting simultaneously, the effects of the allelochemical interaction were lower than the sum of the effects of each compound tested separately, suggesting antagonism.
Keywords: allelopathy; antagonism; soybean; roots; phenolic acids